Step * 1 of Lemma unit-set-presheaf-type


1. SmallCategory
2. cat-ob(C)
⊢ {Yoneda(I) ⊢ _} {AF:A:L:cat-ob(C) ⟶ (cat-arrow(C) I) ⟶ Type × (L:cat-ob(C)
                                                                      ⟶ J:cat-ob(C)
                                                                      ⟶ f:(cat-arrow(C) L)
                                                                      ⟶ a:(cat-arrow(C) I)
                                                                      ⟶ (A a)
                                                                      ⟶ (A (cat-comp(C) a)))| 
                     let A,F AF 
                     in (∀K:cat-ob(C). ∀a:cat-arrow(C) I. ∀u:A a.  ((F (cat-id(C) K) u) u ∈ (A a)))
                        ∧ (∀L,J,K:cat-ob(C). ∀f:cat-arrow(C) L. ∀g:cat-arrow(C) J. ∀a:cat-arrow(C) I. ∀u:A a.
                             ((F (cat-comp(C) f) u)
                             (F (cat-comp(C) a) (F u))
                             ∈ (A (cat-comp(C) (cat-comp(C) f) a))))} 
BY
(Computation THEN EqCD THEN Try (Trivial)) }

1
1. SmallCategory
2. cat-ob(C)
3. Base
4. I@0 Base
5. Base
6. Base
7. Base
8. @0 Base
⊢ f(a) cat-comp(C) I@0 a

2
1. SmallCategory
2. cat-ob(C)
3. AF Base
4. Base
5. Base
⊢ (∀I@0:cat-ob(C). ∀a:Yoneda(I)(I@0). ∀u:A I@0 a.  ((F I@0 I@0 (cat-id(C) I@0) u) u ∈ (A I@0 a)))
∧ (∀I@0,J,K:cat-ob(C). ∀f:cat-arrow(C) I@0. ∀g:cat-arrow(C) J. ∀a:Yoneda(I)(I@0). ∀u:A I@0 a.
     ((F I@0 (cat-comp(C) I@0 f) u) (F f(a) (F I@0 u)) ∈ (A cat-comp(C) I@0 f(a)))) 
(∀K:cat-ob(C). ∀a:cat-arrow(C) I. ∀u:A a.  ((F (cat-id(C) K) u) u ∈ (A a)))
∧ (∀L,J,K:cat-ob(C). ∀f:cat-arrow(C) L. ∀g:cat-arrow(C) J. ∀a:cat-arrow(C) I. ∀u:A a.
     ((F (cat-comp(C) f) u)
     (F (cat-comp(C) a) (F u))
     ∈ (A (cat-comp(C) (cat-comp(C) f) a))))


Latex:


Latex:

1.  C  :  SmallCategory
2.  I  :  cat-ob(C)
\mvdash{}  \{Yoneda(I)  \mvdash{}  \_\}  \msim{}  \{AF:A:L:cat-ob(C)  {}\mrightarrow{}  (cat-arrow(C)  L  I)  {}\mrightarrow{}  Type  \mtimes{}  (L:cat-ob(C)
                                                                                                                                            {}\mrightarrow{}  J:cat-ob(C)
                                                                                                                                            {}\mrightarrow{}  f:(cat-arrow(C)  J  L)
                                                                                                                                            {}\mrightarrow{}  a:(cat-arrow(C)  L  I)
                                                                                                                                            {}\mrightarrow{}  (A  L  a)
                                                                                                                                            {}\mrightarrow{}  (A  J 
                                                                                                                                                    (cat-comp(C)  J  L  I  f 
                                                                                                                                                      a)))| 
                                          let  A,F  =  AF 
                                          in  (\mforall{}K:cat-ob(C).  \mforall{}a:cat-arrow(C)  K  I.  \mforall{}u:A  K  a.
                                                      ((F  K  K  (cat-id(C)  K)  a  u)  =  u))
                                                \mwedge{}  (\mforall{}L,J,K:cat-ob(C).  \mforall{}f:cat-arrow(C)  J  L.  \mforall{}g:cat-arrow(C)  K  J.
                                                      \mforall{}a:cat-arrow(C)  L  I.  \mforall{}u:A  L  a.
                                                          ((F  L  K  (cat-comp(C)  K  J  L  g  f)  a  u)
                                                          =  (F  J  K  g  (cat-comp(C)  J  L  I  f  a)  (F  L  J  f  a  u))))\} 


By


Latex:
(Computation  THEN  EqCD  THEN  Try  (Trivial))




Home Index